ASPEK HISTOPATOLOGIK LIPOSARKOMA - Niniek Hardini (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2020)
Liposarcoma is a malignancy that comes from primitive cells that have differentiation into fat cells. Location of the tumor is usually in the extremities, trunk and retroperitoneum. Liposarcoma is slow growing, deep, painless and large in size. Most sufferers are adults, aged between 40-60 years, a little dominant in men. In children, it tends to occur in the second decade of life. The incidence of liposarcoma in the world is 17% of all soft tissue malignancies. Data in the RSCM shows 70 cases of liposarcoma in a period of 10 years. The etiology of liposarcoma can come from physical factors, chemistry and biology that can be carcinogens in addition to genetic factors as a predisposition to liposarcoma. The diagnosis of liposarcoma is based on history taking and physical examination which begins with complaints of large pains that are painless and grow slowly, supported by radiological and histopathological examination as a determinant of diagnosis. Histopathological features of liposarcoma form the basis of classification, divided into five categories, namely: (1) well differentiated liposarcoma, (2) dedifferentiated liposarcoma, (3) mycid liposarcoma, (4) round cell liposarcoma, (5) pleomorphic liposarcoma. Liposarcoma management in the form of multimodality therapy, a combination of surgery, radiotherapy and chemotherapy. The prognosis of liposarcoma is mainly determined by the histopathologic type, tumor location and tumor size.